(untitled) (Altre Modernità, 2019)
This article approaches the theme of "New Old Slavery" from a study of Afro-Brazilian literature written by women. The idea is to show that black women have lived - and live, since racial prejudice still persists in our society, which is a legacy of the slavery process - for centuries on the slavery of silencing and, through literature, they have been fighting and conquering a space in Brazilian literature from which they give voice to those who, for centuries, have been and continue, even to a lesser extent, being muted and invisible to history, and in this way, a new form of the old slavery is rendered. Through literary art, Afro-Brazilian writers have "blurred" the traditional and official speech when they narrate, from their own perspective, the other version of history that was "forgotten" by the dominant ideology.